An assessment on the implementation of same day antiretroviral therapy initiation in eThekwini clinics, KwaZulu‑Natal, South Africa - Sabina M. Govere; Tawanda Manyangadze; Chester Kalinda; Moses J. Chimbari (AOSIS, 2023)
The World Health Organization (WHO) recom‑ mends same‑day initiation (SDI) of antiretroviral therapy (ART) for all individuals diagnosed with HIV irrespective of CD4+ count or clinical stage. Implementation of program is still far from reaching its goals. This study assessed the level of implementation of same day ART initiation. A longitudinal study was conducted at four primary healthcare clinics in eThekwini municipality KwaZulu‑Natal. Data was collected between June 2020 to October 2020 using a data extrac‑ tion form. Data on individuals tested HIV positive, number of SDI of ART; and clinicians working on UTT program were compiled from clinic registers, and Three Interlinked Electronic Registers.Net (TIER.Net). Non‑governmental organisations (NGO) supporting the facility and services information was collected. Among the 403 individuals who tested HIV positive, 279 (69.2%) were initiated on ART on the same day of HIV diagnosis from the four facilities. There was a significant association between health facility and number of HIV positive individuals initiated on SDI (chi‑square=10.59; P‑value=0.008). There was a significant association between facilities with support from all NGOs and ART SDI (chi‑square=10.18; P‑value=0.015. There was a significant association between staff provision in a facility and SDI (chi‑square=7.51; P‑value=0.006). Urban areas clinics were more likely to have high uptake of SDI compared to rural clinics (chi‑square=11,29; P‑value=0.003). Implementation of the Universal Test and Treat program varies by facility indi‑ cating the need for the government to monitor and standardize implementation of the policy if the program is to yield success.